Preliminary results in the introduction of cranberries - Toshboev Shuhratbek Tursunboevich; Nazhmudinova Dilfuzakhon Sharobidinovna; Berdaliev Husniddin Norkul oglu (Zien Journals, 2022)
The article provides preliminary observations on the process of introduction of cranberries to the conditions of the Coral Sea in Andijan region, the growth of the plant, the formation of side branches and the process of flowering.
Keywords: Cranberry; Vaccinium vitis-idea; artificial growth; root